2008
DOI: 10.1016/j.ejphar.2008.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the interaction between nonsteroidal anti-inflammatory drugs and methotrexate using human organic anion transporter 3-transfected cells

Abstract: Coadministration of methotrexate and nonsteroidal anti-inflammatory drugs (NSAIDs) can cause a pharmacokinetic interaction and a subsequent increase in blood methotrexate concentrations. methotrexate and most NSAIDs are excreted into urine via organic anion transporter 3 (OAT3). The purpose of this study was to evaluate NSAIDs that compete less with methotrexate by using the renal cell line stably expressing human OAT3 (S2-hOAT3) in vitro. We also confirmed the pharmacokinetic interaction of methotrexate with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 40 publications
3
39
0
Order By: Relevance
“…Thus, xenobiotic inhibition of Oat3 may prevent the renal toxicity of some b-lactams; however, inhibition may also limit the concentration of particular b-lactams in renal and postrenal infections, reducing efficacy. Importantly, it is now clear that many b-lactams may increase systemic exposure to competing substrates such as statin drugs (Windass et al, 2007) and methotrexate (Maeda et al, 2008) via interaction on Oat3. Furthermore, these findings indicate that Oat3 may be a major factor limiting brain exposure to b-lactams.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, xenobiotic inhibition of Oat3 may prevent the renal toxicity of some b-lactams; however, inhibition may also limit the concentration of particular b-lactams in renal and postrenal infections, reducing efficacy. Importantly, it is now clear that many b-lactams may increase systemic exposure to competing substrates such as statin drugs (Windass et al, 2007) and methotrexate (Maeda et al, 2008) via interaction on Oat3. Furthermore, these findings indicate that Oat3 may be a major factor limiting brain exposure to b-lactams.…”
Section: Resultsmentioning
confidence: 99%
“…Methotrexate is taken up from the blood via OATs. NSAIDs can inhibit OATs, and when methotrexate and NSAIDs are used together, methotrexate toxicity can occur, manifesting as severe bone marrow suppression (76,77). DDIs at the level of P-glycoprotein (MDR1/ABCB1) in the proximal tubule and elsewhere are thought to explain the well known digoxin-quinidine interaction resulting in digoxin toxicity, including arrhythmias (78).…”
Section: Ddis and Drug-metabolite Interactionsmentioning
confidence: 99%
“…MTX is taken up from blood across the basolateral membrane via organic anion transporters (OATs, SLC22A) 1 and 3 and reduced folate carrier-1 (Sekine et al, 1997;Hosoyamada et al, 1999;Cha et al, 2001;Nozaki et al, 2004), with subsequent excretion across the apical membrane via ATP-dependent efflux pumps, multidrug resistance proteins (MRPs, ABCC) 2 and 4 (Masuda et al, 1997;Chen et al, 2002;van Aubel et al, 2002) and breast cancer-resistant protein (BCRP) Nozaki et al, 2007) into urine. Thus, the competition of renal tubular secretion between MTX and NSAIDs has been thought to be a major cause of the drug interaction (Frenia and Long, 1992;Maeda et al, 2008). With respect to the inhibitory effect of NSAIDs on MTX uptake at the basolateral membrane, many reports have shown that several NSAIDs inhibit the transport of MTX via OAT1 and OAT3 (Uwai et al, 2000;Khamdang et al,2002;Takeda et al, 2002;Nozaki et al, 2004;Maeda et al, 2008).…”
Section: Introductionmentioning
confidence: 99%